Problem of Foundations of the Humanities in the Philosophies of J. S. Mill and W. Dilthey - Juozaitis, Arvydas (Problemos, 1985)
The problem of foundations of the humanities (Geisteswissenschaften) has arisen in the 19th century. It was prompted by methodological shifts in the considerations of human subjectivity. The problem has acquired paramount importance in the philosophy of life, but it was evident to some positivists too. J. S. Mill and W. Dilthey, basing their views on different theoretical presumptions, founded the humanities by working out different interpretations of inner experience, namely, the former – sensualistic one, the latter – irrationalistic one. It is shown in the article how different theoretical presumptions result in different views of the humanities.